2020
DOI: 10.21773/boun.34.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Time-varying return predictability and adaptive markets hypothesis: Evidence on MIST countries from a novel wild bootstrap likelihood ratio approach

Abstract: This paper investigates the evolution of the return predictability (or market efficiency) degree for Mexico, Indonesia, South Korea, and Turkey (MIST) countries and examines whether the findings are consistent with the implications of adaptive markets hypothesis (AMH). For this purpose, the novel wild bootstrap likelihood ratio approach of Kim and Shamsuddin ( 2020) is applied on the monthly data from January 1993 to July 2020 with the rolling sub-sample windows method to determine whether the ability of infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Furthermore, Bozkuş and Kahyaoğlu ( 2020 ) demonstrated the validity of the heterogeneous market hypothesis, whereas Balcı et al ( 2022 ) demonstrated the validity of the fractal market hypothesis in Borsa Istanbul. Meanwhile, Mandacı et al ( 2019 ), Eyüboğlu and Eyüboğlu ( 2020 ), and Özkan ( 2020 ) and Burhan and Acar ( 2021 ) discovered that AMH holds true in the Turkish stock market. Mensi et al ( 2022 ) also examined the asymmetric multifractal structure of the markets during various crisis periods, such as the GFC and COVID-19, using the leading market indices of the Middle East and North Africa (MENA) stock markets, including Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Bozkuş and Kahyaoğlu ( 2020 ) demonstrated the validity of the heterogeneous market hypothesis, whereas Balcı et al ( 2022 ) demonstrated the validity of the fractal market hypothesis in Borsa Istanbul. Meanwhile, Mandacı et al ( 2019 ), Eyüboğlu and Eyüboğlu ( 2020 ), and Özkan ( 2020 ) and Burhan and Acar ( 2021 ) discovered that AMH holds true in the Turkish stock market. Mensi et al ( 2022 ) also examined the asymmetric multifractal structure of the markets during various crisis periods, such as the GFC and COVID-19, using the leading market indices of the Middle East and North Africa (MENA) stock markets, including Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of the Turkish Stock Market was investigated in detail through the studies conducted by Ozkan (2020aOzkan ( , 2020bOzkan ( , 2020cOzkan ( , 2021aOzkan ( , 2021b. Each of the studies focused on different set of markets and through varying tests and timeframes taken the results pointed the Turkish Stock Market having different efficiency levels which varied with time.…”
Section: Literature Reviewmentioning
confidence: 99%